2022
DOI: 10.3934/jimo.2021081
|View full text |Cite
|
Sign up to set email alerts
|

Due-window assignment scheduling with learning and deterioration effects

Abstract: This paper considers single machine due-window assignment scheduling problems with position-dependent weights. Under the learning and deterioration effects of jobs processing times, our goal is to minimize the weighted sum of earliness-tardiness, starting time of due-window, and due-window size, where the weights only depends on their position in a sequence (i.e., positiondependent weights). Under common due-window (CONW), slack due-window (SLKW) and different due-window (DIFW) assignments, we show that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Lv and Wang [18] researched the two-machine flowshop scheduling with the DIFDW and resource allocation. Lin [19] worked on single-machine scheduling with the CONDW, SLKDW and DIFDW. Under position-dependent weights, learning and deterioration effects, they demonstrated that some problems are polynomially solvable.…”
Section: Introductionmentioning
confidence: 99%
“…Lv and Wang [18] researched the two-machine flowshop scheduling with the DIFDW and resource allocation. Lin [19] worked on single-machine scheduling with the CONDW, SLKDW and DIFDW. Under position-dependent weights, learning and deterioration effects, they demonstrated that some problems are polynomially solvable.…”
Section: Introductionmentioning
confidence: 99%